Amyloid β Peptide of Alzheimer’s Disease Downregulates Bcl-2 and Upregulates Bax Expression in Human Neurons - Paradis, Eric (J Neurosci, 1996)
Neuronal apoptosis is a suspected cause of neurodegeneration in Alzheimer’s disease (AD). Increased levels of amyloid β peptide (Aβ) induce neuronal apoptosis in vitro and in vivo. The underlying molecular mechanism of Aβ neurotoxicity is not clear. The normal concentration of Aβ in cerebrospinal fluid is 4 nm. We treated human neuron primary cultures with 100 nm amyloid β peptides Aβ(1–40) and Aβ(1–42) and the control reverse peptide Aβ(40–1). We find that although little neuronal apoptosis is induced by either peptide after 3 d of treatment, Aβ(1–42) provokes a rapid and sustained downregulation of a key anti-apoptotic protein, bcl-2, whereas it increases levels of bax, a protein known to promote cell death. In contrast, the Aβ(1–40) downregulation of bcl-2 is gradual, although the levels are equivalent to those of Aβ(1–42)-treated neurons by 72 hr of treatment. Aβ(1–40) does not upregulate bax levels. The control, reverse peptide Aβ(40–1), does not affect either bcl-2 or bax protein levels. In addition, we found that the Aβ(1–40)- and Aβ(1–42)- but not Aβ(40–1)-treated neurons had increased vulnerability to low levels of oxidative stress. Therefore, we propose that although high physiological amounts of Aβ are not sufficient to induce apoptosis, Aβ depletes the neurons of one of its anti-apoptotic mechanisms. We hypothesize that increased Aβ in individuals renders the neurons vulnerable to age-dependent stress and neurodegeneration.